Emotional labour and job satisfaction of nurses working in public hospitals: testing the mediating role of burnout and moderating role of gender. (16th June 2022) - Soumyaja, Devi; Sowmya, C.S.; Joy, Athena
Emotional labour is the process of managing ones' emotions with the emotional requirements of the job. Emotional labour is considered to be an essential skill in the healthcare sector. The present study investigates the connection between emotional labour strategies (surface and deep level acting emotional labour), burnout and job satisfaction. We surveyed a sample of 341 nurses working in public sector hospitals in Kerala, India. Traditionally, nursing has been considered as a female dominated profession but recently the number of male nurses has increased. Thus the study also aimed to understand the gender differences by considering gender as a moderator. Analyses revealed that burnout fully mediated the relationship between surface acting and job satisfaction. However, burnout had only a partial mediation effect between deep acting emotional labour and job satisfaction. The most important finding of the study through moderated mediation analysis was that gender was found to moderate the indirect effect from surface acting and deep acting to job satisfaction via burnout. For both surface and deep level acting, the positive relationship with burnout was found to be stronger for males than for females.